Learning through play in mathematics lessons - Teokarevic, Dalibor D. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2024)
Of all human activities, the most pleasurable is the game, whether it is sports, computer, social, educational, or some other games. As the game is one of the most important needs of children, it is also the easiest way to introduce students to educational content. That is why learning through play is one of the most powerful motivational teaching methods, which encourages creativity in students expressed through imagination, logical thinking, emotional expression and motivation for work and learning. Learning through play also affects the all-round development of the student's personality, because it affects the cognitive, emotional, social and physical development of the child, preparing him for his future life in the world of adults.
Keywords: Learning; playing; teaching mathematics